Ribotyping Identification of Thermophilic Bacterium from Papandayan Crater - Akhmaloka Akhmaloka; A. Suharto; S. Nurbaiti; I. N. Tika; F. M. Warganegara (Institute for Research and Community Services, Institut Teknologi Bandung, 2006)
A few thermophilic bacteria were isolated from a hot spring located in Papandayan Crater, Garut. One of the organisms showed a well growth at temperature of up to 80 oC. Chromosomal DNA from the organism was isolated and used to amplify 16S rRNA gene fragment. The gene was amplified by a set of universal primers (27F and 1492R) resulting in a 1.5 kb DNA fragment. The gene was cloned and sequenced. The phylogenetic tree, homological analysis, and detailed comparison of the sequences showed that 16S rRNA gene sequence of the Papandayan isolate is unique compared to other known strains, however the sequence had closest similarities with Bacillus caldolyticus and Bacillus caldotenax.